Volume, intensity, and timing of muscle power potentiation are variable - Chaouachi, A.; Poulos, N.; Abed, F.; Turki, O.; Brughelli, M.; Chamari, K.; Drinkwater, E. J.; Behm, D. G. (Applied Physiology, Nutrition, and Metabolism, 2011)
Whereas muscle potentiation is consistently demonstrated with evoked contractile properties, the potentiation of functional and physiological measures is inconsistent. The objective was to compare a variety of conditioning stimuli volumes and intensities over a 15-min recovery period. Twelve volleyball players were subjected to conditioning stimuli that included 10 repetitions of half squats with 70% of 1-repetition maximum (RM) (10 × 70), 5 × 70, 5 × 85, 3 × 85, 3 × 90, 1 × 90, and control. Jump height, power, velocity, and force were measured at baseline, 1, 3, 5, 10, and 15 min. Data were analysed with a 2-way repeated measure ANOVA and magnitude-based inferences. The ANOVA indicated significant decreases in jump height, power, and velocity during recovery. This should not be interpreted that no potentiation occurred. Each dependent variable reached a peak at a slightly different time: peak jump height (2.8 ± 2.3 min), mean power (3.6 ± 3.01 min), peak power (2.5 ± 1.8 min), and peak velocity (2.5 ± 1.8 min). Magnitude-based inference revealed that both the 5 × 70 and 3 × 85 protocol elicited changes that exceeded 75% likelihood of exceeding the smallest worthwhile change (SWC) for peak power and velocity. The 10 × 70 and the 5 × 70 had a substantial likelihood of potentiating peak velocity and mean power above the SWC, respectively. Magnitude-based inferences revealed that while no protocol had a substantial likelihood of potentiating the peak vertical jump, the 5 × 70 had the most consistent substantial likelihood of increasing the peak of most dependent variables. We were unable to consistently predict if these peaks occurred at 1, 3, or 5 min poststimulation, though declines after 5 min seems probable.